Biological treatment of a contaminated gaseous emission from a leather industry in a suspended-growth bioreactor - Carvalho, M. F. (2010)
A suspended-growth bioreactor (SGB) was operated for the treatment of a gaseous stream mimicking emissions generated at a leather industrial company. The main volatile organic compounds (VOCs) present in the gaseous stream consisted of 1-methoxy-2-propanol, 2,6-dimethyl-4-heptanone, 2-butoxyethanol, toluene and butylacetate. A microbial consortium able to degrade these VOCs was successfully enriched. A laboratory- scale SGB was established and operated for 210-d with an 8 h cycle period and with shutdowns at weekends. Along this period, the SGB was exposed to organic loads (OL) between 6.5 and 2.3 £ 102 g h¡1 m¡3. Most of the compounds were not detected at the outlet of the SGB. The highest total VOC removal efficiency (RE) (ca 99%) was observed when an OL of 1.6 £ 102 g h¡1 m¡3 was fed to the SGB. The maximum total VOC elimination capacity (1.8 £ 102 g h¡1 m¡3) was achieved when the OL applied to the SGB was 2.3 £ 102 g h¡1 m¡3. For all the operating conditions, the SGB showed high levels of degradation of toluene and butylacetate (RE t 100%). This study also revealed that recirculation of the gaseous effluent improved the performance of the SGB. Overall, the SGB was shown to be robust, showing high performance after night and weekend shutdown periods.